North Korea's Shadow Economy: A Force for Authoritarian Resilience or Corrosion?*. Issue 3 (15th March 2016) - Dukalskis, Alexander
Abstract: An unofficial or 'shadow' economy like that in contemporary North Korea generates countervailing pressures for a socialist regime. It can buttress the regime by facilitating the cynical use of anti-market laws, alleviating shortages, helping the official economy to function, and creating vested interests in the status quo . On the other hand, the shadow economy can corrode the regime's power by diminishing its control over society, encouraging scepticism about collective ideologies, and providing networks and material that can be used for opposition to the state. This article analyses these tensions in the DPRK, by drawing on 35 semi-structured interviews with North Korean defectors.